The Role of Non-Bank Financial Institution Industry Classes in Improving Students' Accounting Competencies at State Vocational High School 6 Surakarta - Mahastutik, Reva; Jatmika, Surya (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to (1) describe the implementation of the industrial class at SMK Negeri 6 Surakarta, (2) analyze teachers' and students' perceptions of the effectiveness of the industrial class in improving accounting competencies, and (3) identify the factors that influence the effectiveness of the industrial class at SMK Negeri 6 Surakarta. Using a qualitative approach with a case study method, data were collected through interviews, observations, and documentation, and then analyzed through data reduction, data presentation, and conclusion drawing. The results show that the implementation of the Nonbank Financial Institution Industrial Class involves curriculum synchronization with PT Pegadaian, scheduling between theory and practice, learning activities carried out in regular classrooms and rotating practice in the Pegadaian agent mini-laboratory, as well as joint evaluations with PT Pegadaian. Teachers and students perceive this program as effective because transaction practices using the Pegadaian application enhance accounting competencies, discipline, and work readiness through real work experience. The effectiveness of the program is supported by the active role of teachers, student enthusiasm, and the availability of facilities, although it is constrained by the low number of transactions in the Pegadaian application and suboptimal learning facilities.